Being Moved: Dan Halter’s "Rifugiato Mappa del Mondo" ("Refugee Map of the World") Catalyzes Community-Building (AmeriQuests, 2022)
Focusing on Zimbabwe-born/South Africa-based Dan Halter's Rifugiato Mappa del Mondo (Refugee Map of the World) as my commentary's point of departure, the text demonstrates how an art museum can use works from its permanent collection to mobilize and engage in community-building with refugees and migrants. Embedding historical and contemporary discourses on migration topics, displaying works of refugee and migrant artists becomes vital for upholding values of cultural pluralism – and it proves to be meaningful when the work achieves mass resonance among museum visitors. Credits: Dan Halter (Zimbabwean, born 1977). Rifugiato Mappa del Mondo (Refugee Map of the World), 2016. Stitched-together new and used plastic-weave shopping bags. 7 (unique) from a series of 8. Overall: 72 x 150 inches (182.88 x 381 cm). Collection Buffalo AKG Art Museum. By Exchange: Elisabeth H. Gates Fund, James G. Forsyth Fund, Fellows for Life Fund, George Cary Fund and Gift of Mr. and Mrs. Lucien Garo, 2016 (2016:4). © Dan Halter. Image courtesy of the artist and WHATIFTHEWORLD.